Challenges and advances in cervix cancer treatment in elder women. (March 2020) - Kissel, M.; Rambeau, A.; Achkar, S.; Lecuru, F.; Mathevet, P.
Highlights: There is a strong tendency towards undertreatment of elder patients with cervix cancer. Cervix cancer treatment is a true challenge in elder women. Some technical advances increase the tolerability of the treatment in elder patients. The geriatric oncologist is a partner of choice in this situation. There are few reasons to justify that elder women do not receive an appropriate treatment. Abstract: With population ageing, cancer treatments in elder patients is becoming a true public health care issue. There is an authentic dilemma between patient's frailty, residual life expectancy and the toll that take anticancer treatments. Since elder patients are almost always excluded from clinical trials, it is hard to get robust scientific data on the tolerability of oncologic treatments and to set in place recommendations. Cervix cancer is traditionally diagnosed in younger women but it has a 2nd incidence peak between 60 and 70 years old. Cervix cancer in elder patients is a subject to many questions in terms of screening and is a therapeutic challenge. This article reviews literature data on these different aspects, from screening to surgery, from radiotherapy to brachytherapy, from chemotherapy to supportive care, from immunotherapy to geriatric assessment. We tried to show how modern therapeutic innovations may benefit elder patients. Expected benefits in terms of efficacy and toxicity may overcome the long-lasting tendency to undertreatment in elder patients and improve their quality of life after cancer treatment. In 2020, there seems to be less and less reasons justifying that elder women with cervix cancer may not receive the appropriate treatment.